Effect of Ta buffer layer on the structural and magnetic properties of stoichiometric intermetallic FeAl alloy - Sunayana Bhardwaj; Prashant Kumar; Ram Krishna Ghosh; Bijoy K. Kuanr (AIP Advances, 2024)
The magnetostructural phase transition in Fe50Al50 alloy with chemically ordered paramagnetic B2 and disordered ferromagnetic (FM) A2 phase has applications in spintronics such as phase-change magnetic memory and magnonic devices. We first conducted a systematic first-principles density functional theory study of the A2 and B2 phases in the Fe50Al50 alloy. A theoretical understanding of this equiatomic alloy’s electronic and spin-dynamical properties leads us to the experimental exploration of the FM A2 phase. Therefore, we deposit the 50 nm Fe50Al50 alloy thin film using sputtering and investigate the influence of the Ta buffer layer on its structural and magnetic properties. Our results reveal that the film with a buffer layer exhibits the A2 phase with appreciably higher saturation magnetization (848 emu/cc) than the film without a buffer layer (576 emu/cc). However, the surface roughness and Gilbert damping (α) slightly increase with the presence of the buffer layer from 0.41 to 0.56 nm and 4.35 × 10−3–4.94 × 10−3, respectively. The enhancement in α is due to extrinsic contributions induced by surface inhomogeneities.